Diversi Sebagai Aplikasi Restorative Justice Dalam Sistem Peradilan Pidana Anak Di Indonesia - tri susilowati (Fakultas Hukum Universitas Darul Ulum, 2012)
As we know, that there is a real act of dr aspect there is no difference between criminal do not minors with criminal offenses committed by adults. Which can distinguish between the two is on the perpetrators themselves.The difference involves the question of motivation for their actions. Judging from the motivation to do a crime, in general, a child who commits an offense is not based on the motivation of evil (evil mill / evil mind) who came dr child itself.On the basis of that, children who deviate from social norms, to their understanding as the